2019
DOI: 10.1589/jpts.31.223
|View full text |Cite
|
Sign up to set email alerts
|

A prophylactic effect of local vibration on quadriceps muscle fatigue in non-athletic males: a randomized controlled trial study

Abstract: [Purpose] This study was conducted to investigate the immediate prophylactic effects of local vibration on quadriceps muscle fatigue in young non-athletic males. [Participants and Methods] Thirty healthy young males were randomly assigned to vibration and sham control groups. Participants in the local vibration group received a single session vibration (2 minutes, 30 Hz). They also in the control group received a 2-minute vibration, while the vibration system was off. MVC, RMS and median frequency of EMG findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, foam rolling or vibration interventions might improve muscular endurance in the lower limbs. For example, a study revealed that vibration intervention on quadriceps muscle significantly increased the quadriceps muscle time to fatigue (27). Moreover, after a foam rolling intervention, the magnitude of the knee extension maximal isometric voluntary force reduction after fatiguing exercise was lower than that in the control intervention (11).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, foam rolling or vibration interventions might improve muscular endurance in the lower limbs. For example, a study revealed that vibration intervention on quadriceps muscle significantly increased the quadriceps muscle time to fatigue (27). Moreover, after a foam rolling intervention, the magnitude of the knee extension maximal isometric voluntary force reduction after fatiguing exercise was lower than that in the control intervention (11).…”
Section: Discussionmentioning
confidence: 99%